2020
DOI: 10.1177/0042098020908715
|View full text |Cite
|
Sign up to set email alerts
|

Unpacking the advanced producer services complex in world cities: Charting professional networks, localisation economies and markets

Abstract: Limited empirical evidence in support of world-city formation has been the ‘dirty little secret’ of the eponymous research area. Since the late 1990s, inspired by Sassen’s account of The Global City, the field focused on advanced producer services (APS) firms as primary actors in world-city formation. While generating robust insights into the shifting geographies of world cities, empirical attention has mostly focused on mapping inter-urban world city networks formed by APS firms. Despite a rich literature on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 51 publications
1
17
0
2
Order By: Relevance
“…That is, financiers, lawyers, accountants, consultants, together perform an economic function that is more than the sum of its parts, like bringing an IPO into being (Pan et al, 2020). In a recent article, Bassens et al (2020) confirm the existence of the APS complex through an analysis of its internal relations and note that it is particularly the 'para-financial' complex centred around finance, law and accountancy that exhibits the characteristics of an intertwined cluster. W� ojcik (2020) also confirms that finance has increasingly been the 'propulsive actor' that determines the direction and strategy of the APS complex as a whole.…”
Section: The Aps Complex and The Extraction Of Class Monopoly Rentsmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, financiers, lawyers, accountants, consultants, together perform an economic function that is more than the sum of its parts, like bringing an IPO into being (Pan et al, 2020). In a recent article, Bassens et al (2020) confirm the existence of the APS complex through an analysis of its internal relations and note that it is particularly the 'para-financial' complex centred around finance, law and accountancy that exhibits the characteristics of an intertwined cluster. W� ojcik (2020) also confirms that finance has increasingly been the 'propulsive actor' that determines the direction and strategy of the APS complex as a whole.…”
Section: The Aps Complex and The Extraction Of Class Monopoly Rentsmentioning
confidence: 99%
“…Key in this notion is that the strategic positioning within financial networks (Van Meeteren and Bassens, 2016) enables the APS complex as a fraction of capital to extract class-monopoly rents (Harvey, 1974) from the wider economy. The APS complex, in general and tangibly in its local manifestations in financial centres, is comprised of strong formal and informal interdependencies within and between APS sectors, with finance acting as the crucial intermediary (Bassens et al, 2020). However, the relation between these interdependencies and rent extraction remains unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…While focusing on the location patterns of such firms, several studies found different location choices among APS sectors at the local city scale. (e.g., Vandermotten and Roelandts 2006;Bassens et al 2020;Chong and Pan 2020;Waiengnier et al 2020). Waiengnier et al's (2020) study on Brussels, for example, shows that the location preference, and therefore the concentration of firms, depends on the size of the firm and the service they provide.…”
Section: Conceptual Background and Hypothesesmentioning
confidence: 99%
“…Due to these factors, it should not be a surprise that AMC has developed in the Global Cities famously described by Sassen (2001Sassen ( [1991): New York, London, Paris, and Tokyo, among others. It is in these cities where the "command and control" of AMC takes place, activities whose "path-dependent pull" leads to "advanced accumulation [and thus] deepening global core-periphery structures" (Bassens et al, 2021(Bassens et al, : 1288(Bassens et al, -1289.…”
Section: Advanced Producer Services and Asset Manager Capitalismmentioning
confidence: 99%
“…Likewise, what roles do the formal and informal structures linking these professionals play in the development of new niches, products, and legislation? Lastly, do the OFC's various actors make up "an industrial complex, marked by stable formal trading links driving location behaviour, or [do] clusters rely on more informal club-like structures where access depends on experience, routine interaction, personal relations and trust" (Bassens et al, 2021(Bassens et al, : 1291?…”
Section: My Study Within the Literaturementioning
confidence: 99%